2021
DOI: 10.1038/s41467-021-25017-4
|View full text |Cite
|
Sign up to set email alerts
|

Closing the methane gap in US oil and natural gas production emissions inventories

Abstract: Methane (CH4) emissions from oil and natural gas (O&NG) systems are an important contributor to greenhouse gas emissions. In the United States, recent synthesis studies of field measurements of CH4 emissions at different spatial scales are ~1.5–2× greater compared to official greenhouse gas inventory (GHGI) estimates, with the production-segment as the dominant contributor to this divergence. Based on an updated synthesis of measurements from component-level field studies, we develop a new inventory-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 40 publications
4
114
1
Order By: Relevance
“…Lu21 find higher oil-gas emissions for the US and Canada compared to GFEI v1 with high averaging kernel sensitivities for both countries. Many past studies in the US have found an underestimate of oil-gas emissions in the US national inventory (Alvarez et al, 2018;Cui et al, 2019;Maasakkers et al, 2019Rutherford et al, 2021), and similar underestimates have been shown for Canada's national inventory (Johnson et al, 2017;Atherton et al, 2017;Baray et al, 2018Baray et al, , 2021Chan et al, 2020;Scarpelli et al, 2022;MacKay et al, 2021;Tyner and Johnson, 2021). These underestimates are not addressed in the more recent versions of the national inventories as used in GFEI v2 (Table 2).…”
Section: Resultsmentioning
confidence: 56%
“…Lu21 find higher oil-gas emissions for the US and Canada compared to GFEI v1 with high averaging kernel sensitivities for both countries. Many past studies in the US have found an underestimate of oil-gas emissions in the US national inventory (Alvarez et al, 2018;Cui et al, 2019;Maasakkers et al, 2019Rutherford et al, 2021), and similar underestimates have been shown for Canada's national inventory (Johnson et al, 2017;Atherton et al, 2017;Baray et al, 2018Baray et al, , 2021Chan et al, 2020;Scarpelli et al, 2022;MacKay et al, 2021;Tyner and Johnson, 2021). These underestimates are not addressed in the more recent versions of the national inventories as used in GFEI v2 (Table 2).…”
Section: Resultsmentioning
confidence: 56%
“…3 A, 4 A). From previous studies, CH 4 emissions in oil/gas production regions have been traced to a variety of sources: storage tanks 13 , 51 , dehydrators 22 , liquid unloading 52 , gathering stations 53 , pneumatic controllers 54 , or other equipment such as connectors or pipelines 55 . Higher gas production has been suggested to subject the aforementioned equipment to more throughput and thus higher pressure, thereby leading to CH 4 emissions that track production 56 .…”
Section: Discussionmentioning
confidence: 99%
“…CH 4 emissions from oil and gas infrastructure in the U.S. have attracted growing scientific and policy attention as horizontal drilling and hydraulic fracturing significantly boosted U.S. production of oil and natural gas since the early 2000s, revolutionizing the nation’s energy production capabilities 10 . The past decade’s worth of research have revealed that: (a) Emissions can be dominated by a small number of sources (“super-emitters”), often associated with abnormal conditions or malfunctioning equipment 11 13 ; and (b) inventories underestimate CH 4 emissions, primarily in the production sector of the oil/natural gas supply chain 14 . Estimates point to emissions from the U.S. oil and natural gas supply chain to be 2.3% of the U.S. gas production 14 and a significant fraction (over 30%) of the entire anthropogenic U.S. CH 4 emissions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous estimates of global CH 4 isotopic signatures from the exploitation of fossil fuels weighted the source signatures from one basin by its fuel production (Schwietzke et al, 2016). Recent work suggest that fuel production is not a reliable proxy to estimate CH 4 fugitive emissions (Zavala-Araiza et al, 2015;Alvarez et al, 2018;Rutherford et al, 2021;Chen et al, 2021;Maazallahi et al, 2021). Thus, the most relevant sampling locations would be ideally related to estimated emission rates from top-down measurements, instead of production or bottom-up emission estimates.…”
Section: Global Data Overview and Representativenessmentioning
confidence: 99%
“…Users need to define the dominant CH 4 sources impacting an area, as well as the relative source type emission rates. Emission inventories provide such estimates, but top-down approaches are essential to identify potential biases and evaluate the bottom-up approaches (Alvarez et al, 2018; Etiope and 300 Schwietzke, 2019;Rutherford et al, 2021;Stavert et al, 2021).…”
Section: Global Data Distributionmentioning
confidence: 99%